Desire in Paul's undisputed epistles semantic observations on the use of epithymeō, ho epithymētēs, and epithymía in Roman imperial texts - Bowden, Andrew M. 1984-; Ludwig-Maximilians-Universität München; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2020)
Glaubt der Apostel Paulus, dass diejenigen mit »Verlangen« immerzu negative Ziele anstreben? Gibt es Fälle, in denen er dem »Verlangen« etwas Positives abgewinnen kann? Verwendet Paulus diesen Begriff anders als andere kaiserzeitliche Autoren? Ist »Verlangen« immer auf Objekte bezogen, die mit Sex zu tun haben? In dieser Studie veranschaulicht Andrew Bowden Paulus' Gebrauch des »Verlangens« im Lichte seiner Verwendung in Texten der Kaiserzeit und wirft ein neues Licht auf dieses oft missverstandene Konzept.
In this study, Andrew Bowden analyzes Paul's use of »desire« (ἐπιθυμέω, ἐπιθυμητής, and ἐπιθυμία) in his undisputed epistles. After introducing critical research on these lexemes, the author applies John Lyons's theory of semantic analysis to the use of ἐπιθυμέω κτλ in Roman imperial texts. Based on these observations, he makes a hypothesis concerning the common co-occurrences of »desire« in Roman imperial texts, its antonyms, the objects it longs for, and its use within metaphorical discourse. This hypothesis is then tested by looking at the use of »desire« in Dio Chrysostom, Epictetus, Lucian of Samosata, the Cynic epistles, and Second Temple Jewish texts. Andrew Bowden illustrates how, contrary to the view of many scholars, these Roman imperial authors consistently mention positive objects of »desire.« He then applies these findings concerning »desire« to Paul, yielding important and sometimes unexpected discoveries.
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Divine; Johann Jakob Griesbach; Wissenschaftliche Untersuchungen zum Neuen Testament 2. Reihe; Schriftgebrauch; bedeutende Rechtswissenschaftler; Valentinianism; Sexual objects; Obtaining a desire; Positive objects; Slavery to a master; Pleasure; Neues Testament; Array; Hochschulschrift